(untitled) - Wind, Yoram (Hoboken, New Jersey, 2016)
Radically alter the impact of your advertising by changing your mindset Beyond Advertising offers concrete advice for actions to take and mindsets to adopt that will radically alter the impact of advertising--both for advertising professionals and target audiences. An ambitious book with insight from over 200 leading executives, innovators, and academics, this text paints a picture of what the future of advertising may look like by 2020. Most importantly, it provides concrete guidance regarding the changes you can make to your approach in order to thrive in an evolving industry, and explains what you can do differently now to create effective advertising across all consumer touchpoints. Advertising relies upon the engagement of target audience members to be successful, and achieving this engagement is becoming both easier and more difficult as communication channels change to keep up with the latest technology. Retaining a dynamic, flexible approach to advertising--and understanding where to make changes to your methods--is the only way to stay relevant in such a quickly moving industry. Visualize the evolution of the advertising industry, and understand how it may change in the coming decade Avoid the mistake of failing to change your approach to advertising as the industry evolves Identify the concrete actions you can take right now to improve your results Discover the RAVES method of advertising Beyond Advertising is a forward-thinking text that every advertising professional needs to maintain a level of relevancy as the industry continues to evolve
Keywords: Quảng cáo,Advertising